Identification of three classes of heteroaromatic compounds with activity against intracellular Trypanosoma cruzi by chemical library screening. - Esther Bettiol; Marie Samanovic; Andrew S Murkin; Jayne Raper; Frederick Buckner; Ana Rodriguez (PLoS Neglected Tropical Diseases, 2009)
The development of new drugs against Chagas disease is a priority since the currently available medicines have toxic effects, partial efficacy and are targeted against the acute phase of disease. At present, there is no drug to treat the chronic stage. In this study, we have optimized a whole cell-based assay for high throughput screening of compounds that inhibit infection of mammalian cells by Trypanosoma cruzi trypomastigotes. A 2000-compound chemical library was screened using a recombinant T. cruzi (Tulahuen strain) expressing beta-galactosidase. Three hits were selected for their high activity against T. cruzi and low toxicity to host cells in vitro: PCH1, NT1 and CX1 (IC(50): 54, 190 and 23 nM, respectively). Each of these three compounds presents a different mechanism of action on intracellular proliferation of T. cruzi amastigotes. CX1 shows strong trypanocidal activity, an essential characteristic for the development of drugs against the chronic stage of Chagas disease where parasites are found intracellular in a quiescent stage. NT1 has a trypanostatic effect, while PCH1 affects parasite division. The three compounds also show high activity against intracellular T. cruzi from the Y strain and against the related kinetoplastid species Leishmania major and L. amazonensis. Characterization of the anti-T. cruzi activity of molecules chemically related to the three library hits allowed the selection of two compounds with IC(50) values of 2 nM (PCH6 and CX2). These values are approximately 100 times lower than those of the medicines used in patients against T. cruzi. These results provide new candidate molecules for the development of treatments against Chagas disease and leishmaniasis.